Local therapy facilitators working with children with developmental delay in rural and remote areas of western New South Wales, Australia: the 'Outback' service delivery model. Issue 3 (October 2014) - Dew, Angela; Bulkeley, Kim; Veitch, Craig; Bundy, Anita; Lincoln, Michelle; Glenn, Hannah; Gallego, Gisselle; Brentnall, Jennie
Abstract : Australia's dispersed population in rural areas contributes to poor access to therapy services and the inability of the existing rural therapy workforce to meet demand. As a result, rural children with a developmental delay wait a long time for therapy. This paper describes participant perceptions of a therapy facilitation service model that has worked to improve access to therapy for children in these circumstances. The model, given the pseudonym 'Outback', operates in rural and remote areas of western New South Wales. 'Outback' employs local people to work under the guidance of therapists based in larger centres to provide preschool children with developmental delays with access to therapy interventions they might not otherwise receive. A two‐stage case study design involving focus groups and interviews with the director, four therapy facilitators, nine therapists, and seven carers was used. Three themes were identified as central to the service model: 1) being part of the local community; 2) developing therapy facilitator knowledge and skills; 3) improving access to therapy intervention for children in rural and remote areas. The 'Outback' model demonstrates that appropriately supported, local therapy facilitators provide a flexible workforce adjunct that expands the reach of therapists into rural and remote communities and enhances service access for children and their families.